Pendidikan Adab, Kunci Sukses Pendidikan - Machsun, Toha (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2016)
One of the widespread problems of education today is the lack of manners among students. among students. Many students are smart and achievers but lack manners. As a result, there is confusion and misperceptions about science, which then leads to the creation of a lack of manners in society. society, resulting in the emergence of leaders who are not only not only unfit to lead the people, but also lacking in noble morals and and intellectual and spiritual capacity. This is all a result of wrong and misdirected education. Clearly this is not a simple crisis for the world of education in education in this country. To overcome this, adab education is the the solution.